Electric-thermo-mechanical analysis of Joule heating in dilatometric specimens - Herrejón-Escutia, Martin (Strojniški vestnik, 2017)
A mathematical model of Joule heating was developed for an AISI 304 stainless steel in a hollow cylinder dilatometric specimen. The model was developed by means of creating a balance of energy by coupling the generation term due to the Joule heating and the thermal expansion of the specimen. A Newtonian heating system was assumed for a volume element, and it was resolved by means of the finite differences method, generating its own computer code in the Scilab free-license software. The model considers the thermophysical and electrical properties of steel, depending on the temperature. Thermal interactions at the boundary and the linear thermal expansion coefficient were determined by solving the inverse heat conduction problem (IHCP) using the thermal profile and thermal expansion measured experimentally by means of a direct heating device. The model was validated by comparing the thermal response and experimental thermal expansion with simulated responses for different heating rates.
Keywords: dilatometrija; Joulov efekt; matematični modeli; neprekinjeno segrevanje; nerjavno jeklo AISI 304